MULTIDISCIPLINARY TREATMENT OF BONE SARCOMAS: OSTEOSARCOMA, CHONDROSARCOMA, AND EWING SARCOMA (International Seven Journal of Health Research, 2025)
Bone sarcomas, rare and aggressive neoplasms such as osteosarcoma, chondrosarcoma, and Ewing sarcoma, require a multidisciplinary and stratified oncologic and orthopedic approach. This review synthesizes evidence published between 2015 and 2025, addressing the surgical gold standard, neoadjuvant chemotherapy (MAP and VAC/IE regimens), radiotherapy, immune checkpoint inhibitor therapies (ICIs), and the emerging role of circulating molecular biomarkers (ctDNA). Recent studies highlight the importance of morphofunctional imaging characterization (CT and PET-CT) and molecular signatures (e.g., EWS-FLI1 translocation) to guide precise therapeutic decisions.